Comparison of chemical composition, antimicrobial and antioxidant activities of essential oils extracted from different parts of Bambangan (Mangifera pajang) fruit - Lam, Nyee Fan; Abu Bakar, Mohd Fadzelly; Che Rahim, Azlen; Abu Bakar, Fazleen Izzany; Md Sukari, Mohd Aspollah (Asian Publication Corperation, 2018)
Mangifera pajang produces a fruit that is similar to mango, but characterized by brownish exterior colour that contained yellowish flesh and strong mangoish-turpentine aroma. This study identified the chemical composition, antimicrobial and antioxidant activities of the essential oil extracted from flesh, peel and kernel of M. pajang. Different parts of M. Pajang were extracted using hydrodistillation and the essential oils obtained were analyzed using gas chromatography-mass spectrometry (GC-MS). The antioxidant activity was determined spectrophotometrically while the antimicrobial activity was evaluated using disc diffusion method. Total of 56 (flesh), 9 (peel) and 26 (kernel) volatile compounds were identified from the essential oil with the major component obtained were 3-methyl-4-cyclohexene (14.91 %), α-pinene (34.73 %) and linoleic acid (16.58 %), respectively. The essential oils extracted from different parts of the fruit displayed weak inhibition in antimicrobial activity. Antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging showed that essential oil from M. pajang peel displayed the highest antioxidant capacity. It is clear that the essential oils extracted from different parts of M. pajang possess beneficial phytochemicals that can contribute to human's health.